Circulating Long Non-coding RNA ENST00000507296 Is a Prognostic Indicator in Patients with Dilated Cardiomyopathy - Xudong Zhang; Xiang Nie; Shuai Yuan; Huaping Li; Jiahui Fan; Chenze Li; Yang Sun; Yanru Zhao; Huiying Hou; Dao Wen Wang; Chen Chen (Elsevier, 2019)
Background: Long non-coding RNAs (lncRNAs) participate in the pathogenesis of cardiovascular diseases. However, whether circulating lncRNAs serve as dilated cardiomyopathy (DCM) biomarkers remains unclear. Methods: Totally, 266 controls and 818 patients were enrolled. First, microarray-based circulating lncRNA profiling was performed in 10 normal controls and 10 patients with DCM. Second, the top 20 differentially expressed lncRNAs were validated by real-time qPCR in 64 controls and 64 DCM patients. Moreover, lncRNA sequencing was performed in three human heart-derived cell types, and the correlation between circulating lncRNA levels and the severity of heart failure was evaluated in the validated population. The validated two lncRNAs were assessed in 198 DCM patients and 198 matched controls. Finally, the sensitivity and specificity of circulating lncRNA expression in DCM diagnosis were evaluated using receiver-operating characteristic curve analysis, while Cox regression and Kaplan-Meier curve analysis were further performed in 552 DCM patients. Results: Eight candidate lncRNA biomarkers were obtained after microarray screening and real-time PCR validation. Among them, five were validated in the second cohort. However, only the levels of circulating lncRNA ENST00000507296 and ENST00000532365 were significantly correlated with the cardiac function, as well as detectable in at least one of the human heart-derived cell types by lncRNA-seq. Importantly, low circulating ENST00000507296 level was associated with high event-free survival in patients with DCM. Conclusions: Circulating lncRNA ENST00000507296 was a prognostic biomarker in patients with DCM. Keywords: dilated cardiomyopathy, circulating long non-coding RNAs, prognosis